Модель оптимального розміщення базових станцій на основі використання генетичного алгоритму для мережі мобільного зв`язку 5G - Літвінов, О. О. (ХНУРЕ, 2024)
The purpose of the work is to study the genetic approach to solving the problem of optimal placement of base stations in the fifth generation (5G) mobile communication network. An algorithm for optimizing the placement of base stations has been developed based on a genetic approach, as an example of a search procedure, which uses an element of randomness as a means of carrying out the process of finding a solution among many chromosomes. The developed algorithm is implemented as software, which will allow solving large-scale tasks.
Keywords: генетичний алгоритм; оптимальне розміщення базових станцій